Do Absence and Mobility (Transience) Affect Reading Literacy Achievement? - Ratna Rintaningrum (JURNAL SOSIAL HUMANIORA (JSH), 2015)
Reading literacy has been regarded as an important subject taught at the primary school level as it is the foundation for learning across all subject. Australia, as a developed country, has placed great emphasis on the importance of reading literacy in primary schools by establishing various educational policies and undertaking various programs, both for teachers and students, to improve the teaching of reading literacy in school. However, different students have different levels of skill in acquiring reading comprehension. The findings of some studies suggest that there are a number of reasons why some children perform better in reading literacy than others do. Absence and mobility are two factors that are considered to have effect on reading achievement. Both Australia, America and International studies have shown that there is negative relationship between absence, mobility and school achievement.